2002
DOI: 10.1093/cercor/12.8.797
|View full text |Cite
|
Sign up to set email alerts
|

Hearing after Congenital Deafness: Central Auditory Plasticity and Sensory Deprivation

Abstract: The congenitally deaf cat suffers from a degeneration of the inner ear. The organ of Corti bears no hair cells, yet the auditory afferents are preserved. Since these animals have no auditory experience, they were used as a model for congenital deafness. Kittens were equipped with a cochlear implant at different ages and electro-stimulated over a period of 2.0-5.5 months using a monopolar single-channel compressed analogue stimulation strategy (VIENNA-type signal processor). Following a period of auditory exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
139
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(158 citation statements)
references
References 62 publications
15
139
1
3
Order By: Relevance
“…Invasive electrophysiology studies in experimental animals demonstrate that long duration deafness leads to considerable changes in the organization of the auditory cortex. These changes include decoupling of primary from higher order auditory cortex and cross-modal reorganization (Kral et al 2002(Kral et al , 2005Lomber et al 2010). The extent of cortical reorganization depends on timing of deafness onset relative to sensitive periods in early auditory cortical development; it is most pronounced in cases of congenital deafness Kral and Sharma 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Invasive electrophysiology studies in experimental animals demonstrate that long duration deafness leads to considerable changes in the organization of the auditory cortex. These changes include decoupling of primary from higher order auditory cortex and cross-modal reorganization (Kral et al 2002(Kral et al , 2005Lomber et al 2010). The extent of cortical reorganization depends on timing of deafness onset relative to sensitive periods in early auditory cortical development; it is most pronounced in cases of congenital deafness Kral and Sharma 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research effort for this question has been directed towards improving the signal -devising methods, in other words, to limit the spatial spread of electrical excitation on the basilar membrane (for review see (Middlebrooks et al, 2005;Rubinstein, 2004). Given that the spectral receptive fields in the auditory cortex of congenitally or neonatally deaf individuals are also likely to be broad and poorly organized (Kral et al, 2002;Raggio and Schreiner, 1999), it would also be valuable to devise conditioning and/or stimulation protocols that would reduce the spectral integration bandwidth of central auditory neurons. In this way, the spatial resolution of both the signal and the receiver might be improved.…”
Section: Cortical Plasticity and Perceptual Learningmentioning
confidence: 99%
“…Numerous animal studies have shown that brain development relies on developmentally appropriate acoustic stimulation early in life (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Auditory deprivation during critical periods can adversely affect brain maturation and lead to long-lasting neural despecialization in the auditory cortex (AC), whereas auditory enrichment in the early postnatal period can enhance neural sensitivity in the primary AC, as well as improve auditory recognition and discrimination abilities.…”
mentioning
confidence: 99%